Metode-metode tafsir yang ditempuh para ulama - Athallah, Muhammad Farhan (Maliki Interdisciplinary Journal, 2025)
Thuruqu at-tafasir are methods used by scholars to understand the Al-Qur'an as a guide to life according to the commands of Allah SWT. This method aims to bring humans closer to His pleasure. Tafsir methods discussed include tahlili (analytical), ijmali (global), muqoron (comparative), and maudhu'i (thematic) interpretations. This research uses a qualitative descriptive method through literature study of relevant books, journals and articles. Tafsir tahlili explains in depth the content and reasons for the revelation of the verse, suitable for in-depth analysis. Tafsir ijmali provides global explanations, ideal for beginners. Tafsir muqoron compares verses with the opinions of mufassir, both from the Salaf and Khalaf circles. Tafsir Maudhu'i focuses on a particular theme by presenting related verses and explanations. Each method has advantages and disadvantages, but complements each other in explaining the verses of the Koran, as well as enriching the treasures of Islamic scholarship.